Probioticos: potencial para prevenir y curar - Martínez López, Marta; Pacho Jiménez, Sonsoles; Vicario González, Susana (Revista Complutense de Ciencias Veterinarias, 2007)
The History of probiotics soars to ancient times, when there wasn´t even a term to name several nourishments which had beneficial, almost curative effects on the organism. Nowadays, microorganisms whose effects are preventive of some pathologies or which decrease the damage caused by some illnesses are called “probiotics”. Probiotic microorganisms must verify certain specific characteristics such as innocuity, stability, real efficacy, easy administration, digestive tropism or colonization capacity, power to constitute a barrier against infections and improvement of immune usefulness. They are usually consumed preventively since they work by improving the nourish process and producing essential vitamins. However, its real reach is based on specific clinical practice, such as the treatment of digestive, genitourinary or immune pathologies. They even try to palliate the effects of cancer